2019
DOI: 10.1515/hsz-2019-0329
|View full text |Cite
|
Sign up to set email alerts
|

Different signaling and functionality of Rac1 and Rac1b in the progression of lung adenocarcinoma

Abstract: Rac1 is a ubiquitously expressed Rho GTPase and an important regulator of the actin cytoskeleton. Its splice variant Rac1b exhibits a 19-amino acid (aa) in-frame insertion and is predominantly active. Both proteins were described in tumorigenesis or metastasis. We investigated the contribution of Rac1 and Rac1b to tumor progression of human non-small-cell lung adenocarcinoma (NSCLA). Rac1 protein was present in 8/8 NSCLA cell lines analyzed, whereas Rac1b was expressed in only 6/8. In wound-healing assays, enh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
12
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 52 publications
1
12
0
Order By: Relevance
“…Using a panel of PDAC-derived cell lines with a high or low grade of differentiation, we observed that RAC1B was more abundant in well differentiated PDAC lines as opposed to poorly differentiated lines (see Figure 1). A higher abundance of RAC1B expression in more differentiated lines was also observed among a panel of eight lung adenocarcinoma cell lines [33]. This suggested the attractive possibility that the correlation of RAC1B expression with the cells' differentiation grade is not only an epiphenomenon but is functionally involved in maintaining the epithelial phenotype, i.e., by promoting the expression of epithelial genes.…”
Section: Discussionmentioning
confidence: 67%
See 1 more Smart Citation
“…Using a panel of PDAC-derived cell lines with a high or low grade of differentiation, we observed that RAC1B was more abundant in well differentiated PDAC lines as opposed to poorly differentiated lines (see Figure 1). A higher abundance of RAC1B expression in more differentiated lines was also observed among a panel of eight lung adenocarcinoma cell lines [33]. This suggested the attractive possibility that the correlation of RAC1B expression with the cells' differentiation grade is not only an epiphenomenon but is functionally involved in maintaining the epithelial phenotype, i.e., by promoting the expression of epithelial genes.…”
Section: Discussionmentioning
confidence: 67%
“…Rac1b has been reported to promote cell migration and EMT induced by MMP3 [15,16], although this conclusion was based on data from only one epithelial cell line of murine breast origin. In work carried out on a panel of lung adenocarcinoma cell lines we found that ectopic RAC1B expression was associated with increased E-cadherin and decreased Vimentin expression and in contrast to RAC1 was unable to induce EMT and invasive activity in an in vivo chorioallantoic invasion model [33]. Moreover, in a transgenic mouse model of lung adenocarcinoma, Rac1b expression alone was insufficient to drive tumor initiation and was not required for K-ras driven cell proliferation [41].…”
Section: Discussionmentioning
confidence: 99%
“…Paxillin interacts with numerous molecules, controlling the Rho family of GTPases, that are crucial regulators of adhesion dynamics 16,51 . Rac1 GTPase is required for cell migration and its hyperactivation results in cancer invasiveness and progression 52 . Similarly, we also found that knockdown of CDKN2B-AS1 reduced cyclin-D1/D2 expression, thereby decreasing phosphorylation of paxillin and activation of rac1 to inhibit migration/invasion.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, several studies have reported a role of both these two superfamilies of molecules in promoting another key step of the metastatic cascade that is EMT. In response to the same growth factor/cytokines-induced signaling pathways both TRPs and small GTPases are able to induce the up-regulation of mesenchymal-like markers such as vimentin and the down-regulation of epithelial-like markers such as E-cadherin through the direct regulation of transcriptional factors including STAT3, Snail and Twist ( Simon et al, 2000 ; Davis et al, 2014 ; Liu et al, 2014 ; Yang et al, 2015 ; Chen L. et al, 2017 ; Kim et al, 2018 Liu et al, 2019 ; Seiz et al, 2020 ). However, a synergistic cooperation between TRPs and Rho GTPases during the early stage of growth-factor induced EMT is still only speculation, since to the best knowledge of the authors a direct correlation between TRPs and small GTPases effects on EMT has not yet been characterized.…”
Section: Introductionmentioning
confidence: 99%